Bilateral Hip Pain Caused by Adductor Pyomyositis as the Initial Presentation of Chronic Myeloid Leukemia in a 17-Year-Old Child - Ming-Chun Chen; Shang-Hsien Yang; Ting-Kuo Yao; Pau-Nyen Chong; Shu-Huey Chen (Pediatrics and Neonatology)
Pyomyositis is a pyogenic muscular tissue infection mainly occurring in immunocompromised patients. Chronic myeloid leukemia (CML) accounts for only 2–3% of cases of childhood leukemia. Herein, we report on a 17-year-old male with bilateral hip pain caused by adductor pyomyositis before beginning the treatment course of CML. CML was diagnosed by bone marrow chromosome study and was treated initially with imatinib but switched to hydroxyurea 5 days later because of poor cytoreduction response. Subsequently, white blood cell counts decreased gradually; however, the hyperleukocytosis condition resolved very slowly again until we switched back to imatinib use on the 40th day of hospitalization. Pyomyositis was diagnosed by magnetic resonance imaging. Oxacillin was administered to cover Staphylococcus aureus, the most common pathogen of pyomyositis. Bilateral hip pain improved within 72 hours after antibiotic usage, but follow-up magnetic resonance imaging after 15 days of treatment revealed well-defined abscess and osteomyelitis of both femoral heads. Abscess incision and drainage were performed, and cultures of the drained pus grew no microorganisms. The patient completed 5 weeks of oxacillin treatment after the operation and recovered with a full range of motion of both hips. There was no residual disability. This is the first report of bilateral hip pain caused by pyomyositis as the initial presentation of CML. Pyomyositis needs to be considered in the differential diagnosis of hip pain in pediatric patients.